2018
DOI: 10.19103/as.2017.0022.02
|View full text |Cite
|
Sign up to set email alerts
|

Coffee tree growth and environmental acclimation

Abstract: In this chapter, some aspects of coffee growth and development as well as the recent advances in the environmental physiology of growth and production are reviewed. The information deals with both Coffea arabica and C. canephora, which together account for 99% of coffee bean production worldwide. This chapter is organized into sections dealing with vegetative growth, flowering and fruiting, competition between vegetative and reproductive growth, and physiological acclimation to environmental factors including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…The Catuai 62 and IPR 100 cultivars showed higher sensitivity to drought when parasitized, since the plants of these cultivars exhibited photochemical sensitivity (i.e., a reduction in qP). It is noteworthy that IPR 100 showed no increase in qN or NPQ and therefore a potential loss of PSII photochemical efficiency, which may have been caused by oxidative stress (DaMatta, 2018). These results corroborate those of Silva et al (2015), as they indicate that the use of chlorophyll a fluorescence is efficient for the discrimination of the variability between genotypes in response to M. paranaensis .…”
Section: Discussionmentioning
confidence: 99%
“…The Catuai 62 and IPR 100 cultivars showed higher sensitivity to drought when parasitized, since the plants of these cultivars exhibited photochemical sensitivity (i.e., a reduction in qP). It is noteworthy that IPR 100 showed no increase in qN or NPQ and therefore a potential loss of PSII photochemical efficiency, which may have been caused by oxidative stress (DaMatta, 2018). These results corroborate those of Silva et al (2015), as they indicate that the use of chlorophyll a fluorescence is efficient for the discrimination of the variability between genotypes in response to M. paranaensis .…”
Section: Discussionmentioning
confidence: 99%
“…C. arabica L. is a tropical tree responsible for the major worldwide production of coffee ( ICO, 2019 ) and its optimal growth temperature is considered between 18 and 23°C ( Camargo, 1985 ; Teketay, 1999 ). The coffee tree has a periodicity growth habit that closely follows rainfall patterns and, historically, it is considered highly sensitive to climatic changes, especially temperature and drought ( DaMatta and Ramalho, 2006 ; Camargo, 2010 ; DaMatta, 2018 ). Mean temperatures are projected to increase by 2.6–4.8°C ( IPCC, 2013 ; IPCC, 2014 ), which may have serious repercussions on coffee production.…”
Section: Introductionmentioning
confidence: 99%
“…Considering these changing temperatures, select genotypes were identified that outperformed others when exposed to higher annual mean temperatures ( Damatta et al, 2018 ; Marie et al, 2020 ). This suggests there is potentially useful intraspecific variability of thermotolerance in some genotypes and investigation into the molecular mechanisms underlying this variability is warranted ( DaMatta, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The marginal impact of elevated [CO 2 ] on coffee bean quality contrasted with the enhancement of crop yields provided that adequate water supply is available ( DaMatta, 2018 ). Moreover, enhanced [CO 2 ] was found to impair the quality of food harvestable products of several crops, such as wheat, rice, barley, potato (by decreasing protein concentration), and potato (by reducing minerals content) ( Taub, 2010 ; Dietterich et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%